SYNTHESIS AND CHARACTERIZATION ACTIVATED CARBON FROM FISH BONE BY USING ACTIVATOR CaCl2 - Endah Purwanti; Reni Rahmadewi; Vita Efelina; Iwan Sugihartono (Sekolah Tinggi Teknologi Wastukancana, 2020)
Activated carbon is a porous solid containing 85-95% carbon, produced from carbonaceous materials by heating at high temperatures. Activated carbon has a very large surface area so it is suitable for applications requiring large contact areas such as in the adsorption field. Activated carbon can be made from fish bones because fish bones are removed as a waste containing carbon elements that can be used as raw material for making activated carbon. In the manufacture of activated carbon, not only raw materials that need to be considered, but also the process of activation. Activation of the charcoal can be carried out using CaCl2. For charcoal base material from fish bones containing lots of Ca and Mg elements, in addition to using the activator, also the activation process needs to be immersed in H2SO4. Characterization of activated carbons of synthesis include water content test, ash content test, and functional group analysis using FTIR spectroscopy. Based on the results FTIR shows specific peaks for as charcoal activated charcoal based on the literature. Based on the determination of the test water content and ash content obtained by activated charcoal from fish bones has a water content of 4,1% and ash content of 28,1%.